Update on the use of oral octreotide therapy for acromegaly. Issue 4 (3rd July 2016) - Schilbach, Katharina; Schopohl, Jochen
ABSTRACT: Introduction : Somatostatin analogs are most commonly used in pharmacological treatment of acromegaly. Pegvisomant and dopamine agonists are alternatives, which are used to a lesser extent. Dopamine agonists are the only orally applicable medication but are less effective than the other options. For a large number of patients, life-long pharmacotherapy has to be applied and frequent injections represent a reduction of quality of life for many of them. Areas covered : Recently published evidence for the use of oral octreotide therapy for acromegaly. Expert commentary : Oral octreotide is a novel and effective treatment for acromegaly and the side effects have been shown to be comparable to the injectable SSAs. The combination with a transient permeability enhancer allows intestinal permeation but also enables molecules with a size <70 kDa to pass transiently. This does not seem to have an acute or subacute consequence, but the long-term effect is still elusive. Therefore, more long-term trials are desirable.